Law of electronic commercial transactions contemporary issues in the EU, US and China - Wang, Faye Fangfei (Routledge research in IT and E-commerce law, 2014)
"Law of Electronic Commercial Transactions clearly highlights and analyses the main legal obstacles to the establishment of trust and confidence in doing business online. The book compares the legislative frameworks of e-commerce in the EU, US, China and International Organisations. It sets out solutions to modernise and harmonise laws at the national, regional and international levels in response to the current technological developments. The second edition of this book has been fully updated taking into account both the changes in the use of technologies and developments in the law. The new edition provides information on the key legal challenges caused by the increasing popularity of cloud computing, particularly relating to data protection and jurisdiction, and considers how greater legal certainty can be achieved in cloud computing service contracts. The growth in use of automated computing systems to issue international contracts of sale is addressed in terms of what this may mean for the purpose of determining jurisdiction and existing conflict of law rules.The book discusses the recent UNCITRAL ODR Procedural Rules and explores how best to ensure consumer redress in cross-border e-commerce transactions by looking into the detail of the recent Proposal for a Regulation on Online Dispute Resolution for Consumer Protection in the EU. The parts of the book dealing with Internet security and data protection has been expanded taking into account the Proposal of Data Protection Regulation in the EU and explore the conditions of constituting valid consent for processing personal data under the current EU legal framework compared with China and the US.Law of Electronic Commercial Transactions is a clear and up to date account of a fast-moving area of study and as such will be great value to undergraduate and postgraduate students, practitioners and scholars in law and computing"--